Ekstraksi Karoten Dari Spent Bleaching Earth Hasil Dari Proses Bleaching Pengolahan Minyak Goreng - Veronika, Nina; Sari, Voni Indah (Jurnal Sains dan Ilmu Terapan, 2019)
Polytechnic Kampar has a cooking oil plant, where students can learn the real experience of cooking oil processing. Currently, no treatment for the spent bleaching earth as waste that generated in the cooking oil processing. Spent Bleaching Earth resulting from the process of bleaching in the processing still contains substances such as oil and carotene. Extraction of carotenoids substance from spent bleaching earth is one of the alternative recovery carotene from waste.In general, the objectives of this research was to utilize the waste from bleaching process by extracting carotenoids from spent bleaching earth and analyse the extract of carotene. Thus, the utilization of spent bleaching earth can be completed and provide added value to the cooking oil plant.This study was conducted using two (2) types of solvents, namely hexane and acetone to separate carotenes from spent bleaching earth, that obtain optimum conditions for both the solvent and the ratio between the sample and the time of extraction process. The extract of carotene was analyzed using a UV –Vis spectrophotometer .